The Role of Islamic Education Teacher in improving the learning Passion of Students at SMPN 13 Palu - Aan setiawan Aan setiawan (IAI DDI Polewali Mandar, 2020)
This research discusses about the role of Islamic education teachers to develop students learning passion in SMPN 13 Palu. The main problem is how the role of Islamic education teachers in developing passions of the learners in SMPN 13 Palu. Referring to the problem statement of this research, there are 3 research questions; 1) what is the learning approach?, 2) what is the learning method?, and 3) what are the learning strategies used by teachers in SMPN 13 Palu? This research is qualitative research and the subject of this research is Islamic education teacher of SMPN13 Palu. The collection of data consists of three techniques. They are observation, interview, and documentation. The Data analysis is executed by interpreting the whole data and reducing it.